Dynamic enhancement of videogame soundscapes - Pires, Durval (2015)
A game soundscape often includes sounds that are triggered by the game logic according to the player’s actions and to other real time occurrences. The dynamic nature of such triggering events leads to a composition that is not necessarily interesting, at a given moment. We propose a system aiming at the enhancement of the soundscape generated during gameplay. The main component of the system is a module that implements heuristics, which we set to follow principles from Acoustic Ecology and, specifically, the notion of healthy soundscape. In order to inform the heuristics, designers can characterize the sounds being handled by the sound engine, using an API that aims to be accessible and informative about the designer’s intentions. We also present reflections on an essay where a game was remade using the proposed system, which helped us to support the feasibility of the proposed system.